1996
DOI: 10.1111/j.1476-5381.1996.tb15577.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological mechanisms for antiarrhythmic efficacy and positive inotropy of liriodenine, a natural aporphine alkaloid from Fissistigma glaucescens

Abstract: 1 The antiarrhythmic potential and electromechanical effects of liriodenine, an aporphine alkaloid isolated from the plant, Fissistigma glaucescens, were examined. 2 In the Langendorff perfused (with constant pressure) rat heart, at a concentration of 0.3 to 3 gM, liriodenine was able to convert a polymorphic ventricular tachyrhythmia induced by the ischaemiareperfusion (EC50 = 0.3 gM).3 In isolated atrial and ventricular muscle, liriodenine increased the contractile force and slowed the spontaneous beating of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
2
32
1
Order By: Relevance
“…These results suggest that Cinn may exert antiarrhythmic activity by a mode of action similar to class I, III and IV antiarrhythmic agents. The potency of antiarrhythmic activity is comparable to some natural alkaloids such as (-)-caryachine [43] but weaker than N-allylsecoboldine [41] and liriodenine [6].…”
Section: Discussionmentioning
confidence: 68%
“…These results suggest that Cinn may exert antiarrhythmic activity by a mode of action similar to class I, III and IV antiarrhythmic agents. The potency of antiarrhythmic activity is comparable to some natural alkaloids such as (-)-caryachine [43] but weaker than N-allylsecoboldine [41] and liriodenine [6].…”
Section: Discussionmentioning
confidence: 68%
“…This alkaloid was isolated for the first time from Liriodendron tulipifera L., and was subsequently isolated from plant species of many genera (Warthen et al, 1969), mainly found in the families of Magnoliaceae, Annonaceae, Rutaceae, Monimiaceae, and Menispermaceae (Bentley, 2001;Hsieh et al, 2005;Lan et al, 2003;Lin et al, 1994;Nissanka et al, 2001;Woo et al, 1997;Wu et al, 1990). This has a wide range of pharmacological activities, such as activity against Grampositive bacteria (Camacho et al, 2000;Li et al, 2009;Mohamed et al, 2010;Rahman et al, 2005;Waechter et al, 1999), antifungal (Hufford et al, 1980;Khan et al, 2002), antitumoral (Chen et al, 2009Liu et al, 2009), antiarrhythmic activity (Chang et al, 1996(Chang et al, , 2001Chung et al, 2004), antiviral activities (Mohamed et al, 2010) and antiplatelet actions (Chen et al, 1997;Pyo et al, 2003). The objective of this work was to compile information about liriodenine, which may help researcher to understand the efficacy and potency of this alkaloid.…”
Section: Liriodeninementioning
confidence: 99%
“…The in vivo biological studies indicated that through inhibition of the Na + and I to channels, liriodenine suppresses antiarrhythmic activity induced by myocardial ischaemia reperfusion (Chang et al, 1996). An increased concentration of NO limits myocardial ischemia-reperfusion injury.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…and Goniothalamus amuyon (Blanco) Merr., are native to the Taiwan island [28,29]. Our early studies on the Formosan Annonaceous plants focused on alkaloids, which showed diverse biological functions, including cytotoxicity [30], antiplatelet aggregation activity [31], cardiovascular activity [32,33] and antimicrobial activity [34]. Afterwards, diterpenoids, styrylpyrones [12,35,36] and some linear AGEs [37], mono-THF AGEs [38,39], and adjacent bis-THF AGEs [39] were isolated from various parts of the Annona plants in our laboratory.…”
mentioning
confidence: 99%
“…Because substantial amounts of pure samples are required for further biological and clinical studies, a number of total syntheses of AGEs have been reported in the literature since the 1990s. Recent advances in the total syntheses of AGEs include mono-THF AGEs: murisolin (26) [90,91], longicin (27) [92,93], and cis-solamin (28) [94,95], adjacent bis-THF AGEs: bullatacin (14) [96], rolliniastatin 1 (7) [23,97], rollimembrin (29) [97,98], 10-hydroxyasimicin (30) [99,100], membranacin (31) [97,101], asimicin (15) [76,102], longimicin D (32) [103][104], and mucoxin (33) [105,106], non-adjacent bis-THF AGEs: cis-sylvaticin (34) [107,108] and gigantecin (9) [109,110], and others, jimenezin (35) [111,112], mucocin (36) [113,114], pyranicin (37) [115,116], pyragonicin (38) [115,117,118], rollicosin (18) [62,…”
mentioning
confidence: 99%